DEVELOPMENT OF INTERNATIONAL AND NATIONAL LANGUAGES - Shuhrat Kuchimov; Nilufar Ochilova (International Journal of Innovative Technologies in Social Science, 2019)
The article discusses the development of international and national languages, their historical period and role in modern society. Since Uzbekistan is an independent country it is trying to increase the place of Uzbek language among other languages in the world. Currently, there are many foreigners from different countries who are interested in the history of Uzbekistan and its language. We hope that the Uzbek language will develop in the same way as other international languages.